Preparation method of graphene quantum dot-rare earth oxide-titanium dioxide composite material

By preparing GQDs/Gd2O3:Er3+ nanoparticles via a hydrothermal method and modifying the surface of a titanium dioxide nanoarray, the problems of using harmful solvents and cumbersome steps in existing technologies are solved, achieving highly efficient photoelectrocatalytic performance and infrared light absorption, improving photocurrent density and reducing costs.

CN118002110BActive Publication Date: 2025-10-24GUIZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410279464.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2025-10-24
Estimated Expiration
2044-03-12

AI Technical Summary

Technical Problem

Existing technologies require the use of harmful tetrahydrofuran dispersants in the preparation of graphene quantum dot/rare earth oxide nanocomposites, and the synthesis steps are cumbersome, resulting in high costs and low efficiency, and failing to fully utilize infrared light for photocatalysis.

Method used

A solution of GQDs/Gd2O3:Er3+ nanoparticles was prepared by hydrothermal method and then modified with titanium dioxide nanoarrays. This simple surface modification method was used to prepare graphene quantum dot-rare earth oxide-titanium dioxide composite material, avoiding the use of organic solvents and broadening the visible and infrared light absorption range of the material.

Benefits of technology

The photoelectrocatalytic performance of titanium dioxide was improved, with a photocurrent density of 2.15 mA/cm2, which is 3.47 times that of the original TiO2. This broadened the light absorption range, reduced the preparation cost, and simplified the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118002110B_ABST
    Figure CN118002110B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a graphene quantum dot-rare earth oxide-titanium dioxide composite material and belongs to the technical field of functional material preparation. 3+ The GQDs / Gd2O3:Er 3+ nanoparticle solution is deposited on a titanium dioxide nanoarray, dried, and GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite material, that is, the graphene quantum dot-rare earth oxide-titanium dioxide composite material. The application does not need to use an organic solvent for complexing, and the target material can be prepared by using a simple surface modification method. The target material has visible and infrared light absorption characteristics, and can improve the photoelectrocatalytic performance of titanium dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of functional material preparation, and particularly relates to a preparation method of a graphene quantum dot-rare earth oxide-titanium dioxide composite material. BACKGROUND

[0002] Photoelectrochemical (PEC) hydrogen production using solar energy is the main technology with the most application prospects in the technology for obtaining alternative energy sources, and is generally considered as the most ideal hydrogen production approach. However, so far, how to more efficiently and economically use solar energy to produce hydrogen is still a major challenge. Titanium dioxide (TiO2) has the characteristics of rich reserves, low cost, non-toxicity, and high stability and catalytic oxidation, and therefore, TiO2 has a very high application prospect in wastewater degradation, solar energy conversion, photocatalysis and the like. Broadening the light absorption of TiO2 to the visible light and infrared light regions is conducive to improving the catalytic performance.

[0003] Surface modification of TiO2 by quantum dots is a very effective method, because quantum dots, especially graphene quantum dots (GQDs), have many excellent properties such as adjustable band gap, charge carrier selectivity, quantum confinement effect and excellent fluorescence performance. GQDs as a sensitizer can broaden the absorption range of TiO2. In addition, there is interaction between GQDs and the interface of TiO2, which inhibits the recombination of photo-generated electrons of TiO2 and improves the charge transfer efficiency, thereby enhancing the PEC performance of the TiO2 semiconductor-based photocatalyst. However, the modification of TiO2 by GQDs only considers the absorption of visible light, and infrared light accounts for 43% of sunlight, so if the infrared light is fully utilized, the catalytic efficiency of TiO2 will be greatly improved. However, in the preparation of graphene quantum dot / rare earth oxide nanocomposites in the past, graphene quantum dots and rare earth oxides need to be complexed by stirring for a long time through a tetrahydrofuran dispersant, and tetrahydrofuran will produce harmful gases when evaporated, and there are many disadvantages such as more rare earth oxide precipitates and complicated synthesis steps. SUMMARY

[0004] To solve the above technical problems, the application provides a preparation method of a graphene quantum dot-rare earth oxide-titanium dioxide composite material. 3+ Citric acid and Gd2O3:Er 3+ are added to the reaction kettle at one time to obtain GQDs / Gd2O3:Er 3+ without the need for organic solvents for complexation. A simple surface modification method is adopted to prepare GQDs / Gd2O3:Er 3+ The nanocomposite is drop-coated on the surface of the titanium dioxide nanometer array, dried in an oven to prepare GQDs / Gd2O3:Er 3+The graphene quantum dot-rare earth oxide-titanium dioxide nanocomposite material is simple, non-toxic and low in economic cost, the target material can be prepared by using a simple surface modification method without complexation of an organic solvent, and the target material has visible and infrared light absorption characteristics, and can improve the photoelectric catalytic performance of titanium dioxide. In a word, the graphene quantum dot-rare earth oxide-titanium dioxide nanocomposite material has the characteristics of simple process, mild reaction condition and easy operation.

[0005] To achieve the above object, the application provides the following technical scheme.

[0006] A preparation method of a graphene quantum dot-rare earth oxide-titanium dioxide composite material, a GQDs / Gd2O3:Er 3+ nanoparticle solution is prepared by a hydrothermal method. 3+ The GQDs / Gd2O3:Er 3+ nanoparticle solution is deposited on a titanium dioxide nanometer array, dried, and the graphene quantum dot-rare earth oxide-titanium dioxide nanocomposite material is obtained.

[0007] Further, the GQDs / Gd2O3:Er 3+ nanoparticle solution is prepared by the following method:

[0008] The soluble gadolinium salt and the soluble erbium salt are mixed, and then the mixture is uniformly stirred by magnetic stirring after the addition of diethylene glycol, and then the mixture is continuously stirred after the addition of a sodium hydroxide solution, so that a Gd2O3:Er 3+ nanoparticle solution (a nanoparticle solution in which gadolinium oxide doped with erbium is suspended) is synthesized.

[0009] The Gd2O3:Er 3+ nanoparticle solution is dried to obtain a powder, and the powder is ground and calcined to obtain Gd2O3:Er 3+ nanoparticles.

[0010] The Gd2O3:Er 3+ nanoparticles, citric acid (CA) and water are mixed, and a GQDs / Gd2O3:Er 3+ nanoparticle solution is prepared by a hydrothermal method.

[0011] Further, the soluble gadolinium salt is gadolinium chloride hexahydrate, and the soluble erbium salt is erbium chloride hexahydrate.

[0012] Further, the calcination temperature is 600-800 DEG C, and the time is 2h.

[0013] Further, the mass ratio of the Gd2O3:Er 3+ nanoparticles to citric acid is 1:20.

[0014] Further, the GQDs / Gd2O3:Er is prepared by a hydrothermal method 3+ The temperature of the hydrothermal reaction is greater than or equal to 200 DEG C, and the time of the hydrothermal reaction is greater than or equal to 6 hours.

[0015] Further, the preparation method of the titanium dioxide nanometer array is as follows:

[0016] Hydrochloric acid and deionized water are mixed, and then titanium isopropylate (TTIP) is added drop by drop, and the reaction liquid A is prepared by stirring uniformly;

[0017] The substrate is mixed with the reaction liquid A and subjected to a hydrothermal reaction, and then the substrate surface is taken out and washed to obtain the titanium dioxide nanometer array.

[0018] Further, in the preparation method of the titanium dioxide nanometer array, the volume ratio of the titanium isopropylate, the deionized water and the hydrochloric acid is 1:30:30.

[0019] The temperature of the hydrothermal reaction is greater than or equal to 180 DEG C, and the time of the hydrothermal reaction is greater than or equal to 12 hours.

[0020] The substrate is FTO conductive glass.

[0021] Further, the GQDs / Gd2O3:Er 3+ The method for depositing the GQDs / Gd2O3:Er 3+ Nanoparticle solution on the titanium dioxide nanometer array is drop-coated, and then dried in an oven.

[0022] The application provides a GQDs / Gd2O3:Er 3+ Nanocomposite, which can broaden infrared light absorption. 3+ The Gd2O3:Er can be converted into ultraviolet light and visible light for being absorbed by the titanium dioxide, and the nanocomposite also has the advantages of a half-filled electronic configuration, high adsorption capacity and large red shift of a rare earth material.

[0023] The application also provides application of the graphene quantum dot-rare earth oxide-titanium dioxide composite material prepared by the method to photoelectric hydrogen production.

[0024] Compared with the prior art, the application has the following advantages and technical effects:

[0025] The application prepares the GQDs / Gd2O3:Er 3+ Nanocomposite by a hydrothermal method, avoids generation of harmful substances and complicated steps, and is low in economic cost. 3+The nanocomposite contains quantum dots for visible light absorption and excellent electrical conductivity, and erbium-doped gadolinium oxide for broadening the light absorption of infrared light, ensuring that the visible light of titanium dioxide is fully absorbed while broadening the absorption of infrared light. Through GQDs / Gd2O3:Er 3+ modification of TiO2, the GQDs / Gd2O3:Er 3+ / TiO2 photoelectric current density is as high as 2.15 mA / cm 2 , which is 3.47 times that of the original TiO2(0.62 mA / cm 2 ). Compared with single GQDs and Gd2O3:Er 3+ modified TiO2, the GQDs / Gd2O3:Er 3+ / TiO2 photoelectric current is increased by 21.5% and 28.0% respectively on the basis of GQDs / TiO2(1.77 mA / cm 2 ) and Gd2O3:Er 3+ / TiO2(1.68 mA / cm 2 ). Meanwhile, the performance enhancement mechanism is clarified through theoretical calculation, which provides a useful reference for the development of photocatalysts based on heterostructures. BRIEF DESCRIPTION OF DRAWINGS

[0026] The accompanying drawings, which form a part of this application, are included to provide a further understanding of the application and are incorporated in and constitute a part of this application. The embodiments illustrated in the drawings are provided to explain the present application and are not intended to limit the present application. In the drawings:

[0027] Figure 1 is a composite model of the GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite obtained in Example 1;

[0028] Figure 2 is a differential charge density map of the GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite obtained in Example 1;

[0029] Figure 3 (a) and (b) are band structure diagrams of TiO2 and GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite respectively, (c) and (d) are state density diagrams of TiO2 and GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite respectively;

[0030] Figure 4 is a preparation flowchart of the graphene quantum dot-rare earth oxide-titanium dioxide composite material of Example 1;

[0031] Figure 5GQDs / Gd2O3:Er prepared for Example 1 3+ SEM and TEM images of GQDs / Gd2O3:Er / TiO2nanocomposites, wherein (a) is the SEM image of TiO2, (b) is the SEM image of GQDs / Gd2O3:Er / TiO2 3+ SEM image of GQDs / Gd2O3:Er / TiO2, (c) is the TEM image of GQDs / Gd2O3:Er / TiO2 3+ TEM image of GQDs / Gd2O3:Er / TiO2, (d) is the HRTEM image of GQDs / Gd2O3:Er / TiO2 3+ HRTEM image of GQDs / Gd2O3:Er / TiO2 (the inset is the SAED image);

[0032] Figure 6 GQDs / Gd2O3:Er prepared for Example 1 3+ EDS spectrum of GQDs / Gd2O3:Er / TiO2nanocomposites;

[0033] Figure 7 GQDs / Gd2O3:Er prepared for Example 1 3+ XRD pattern of GQDs / Gd2O3:Er / TiO2nanocomposites;

[0034] Figure 8 GQDs / Gd2O3:Er prepared for Example 1 3+ Infrared spectrum of GQDs / Gd2O3:Er nanoparticles;

[0035] Figure 9 GQDs / Gd2O3:Er prepared for Example 1 3+ XPS pattern of GQDs / Gd2O3:Er / TiO2nanocomposites, wherein (a) is the X-ray photoelectron full spectrum and Ti2p local amplification image, (b) is the C1s spectrum, (c) is the O1s spectrum, (d) is the Ti2p spectrum, (e) is the Gd4d spectrum, (f) is the Er4d spectrum;

[0036] Figure 10 GQDs / Gd2O3:Er prepared for Example 1 3+ Infrared spectrum of GQDs / Gd2O3:Er nanoparticles (a) and GQDs / Gd2O3:Er / TiO2nanocomposites (b); 3+ UV-Vis absorption spectrum of GQDs / Gd2O3:Er / TiO2nanocomposites (b);

[0037] Figure 11 Photoluminescence spectrum of TiO2and GQDs / Gd2O3:Er prepared for Example 1 3+ Photoluminescence spectrum of GQDs / Gd2O3:Er / TiO2nanocomposites;

[0038] Figure 12 Photoluminescence spectrum of TiO2and GQDs / Gd2O3:Er prepared for Example 1 3+The photocurrent curve (a), the transient photocurrent curve (b), the electrochemical impedance curve (c) and the photoelectric conversion efficiency curve (d) of the GQDs / TiO2 nanocomposite prepared for TiO2 and Comparative Example 1;

[0039] Figure 13 The photocurrent curve (a), the transient photocurrent curve (b), the electrochemical impedance curve (c) and the photoelectric conversion efficiency curve (d) of the GQDs / TiO2 nanocomposite prepared for TiO2 and Comparative Example 1;

[0040] Figure 14 The XRD diffraction pattern of Gd2O3:Er 3+ The photocurrent curve (a), the transient photocurrent curve (b), the electrochemical impedance curve (c) and the photoelectric conversion efficiency curve (d) of the GQDs / TiO2 nanocomposite prepared for TiO2 and Comparative Example 1;

[0041] Figure 15 The XRD diffraction pattern of Gd2O3 for Example 1 (800℃), Example 6 (600℃) and Comparative Example 3 (1000℃). DETAILED DESCRIPTION

[0042] The detailed description particularly refers to various exemplary embodiments of the application, which are illustrative of the various aspects thereof, and are not meant to limit the present application in any way, which can be embodied in other ways, and the scope of the present application is not limited to the specific illustrative embodiments described herein.

[0043] It should be understood that the terms used herein are merely for the purpose of describing particular embodiments and are not intended to limit the present application. In addition, for numerical ranges in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is specifically disclosed. Each smaller range within a stated range and between the stated values or intermediate values in the stated range is also encompassed. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.

[0044] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although preferred methods and materials are described, any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application. All documents mentioned herein are incorporated by reference to disclose and describe the methods and / or materials in connection with which the documents are cited. In the case of conflict between the present specification and any document incorporated by reference, the present specification will control.

[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.

[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0047] Unless otherwise specified, the room temperature in the embodiments of the present invention is 25±2°C.

[0048] All raw materials used in the examples of the present invention are commercially available.

[0049] The technical solution of the present invention is further illustrated by the following examples.

[0050] Example 1

[0051] S1: Preparation of titanium dioxide (TiO2) nanoarrays

[0052] Mix 30 mL of hydrochloric acid and 30 mL of deionized water, then add 1 mL of isopropyl titanate (TTIP) dropwise and stir for 10 minutes to prepare reaction solution A. FTO conductive glass and reaction solution A were placed in a reactor and hydrothermally reacted at 180°C for 12 hours. After the reaction, the surface of the FTO conductive glass substrate was removed and washed to obtain titanium dioxide nanoarrays.

[0053] S2: Preparation of GQDs / Gd2O3:Er 3+ Nanocomposites

[0054] 1.695 g of gadolinium chloride hexahydrate (GdCl3·6H2O) and 0.092 g of erbium chloride hexahydrate (ErCl3·6H2O) were mixed and placed in a distillation flask. 200 mL of diethylene glycol was added and magnetic stirring was carried out at room temperature for 12 h. 1.44 mL of 10 mol / L sodium hydroxide solution was added and magnetic stirring was continued for 6 h to synthesize a suspension of Gd2O3:Er 3+ Prepared nanoparticle solution with Gd2O3:Er 3+ The nanoparticle solution was dried in a vacuum oven at 120 °C for one week, the powder was collected and ground, and calcined in a muffle furnace at 800 °C for 2 h to obtain Gd2O3:Er 3+ Nanoparticle powder. Take 0.1g Gd2O3:Er 3+GQDs / Gd2O3:Er was synthesized by adding 0.5 g of GQDs, 2 g of citric acid (CA) and 30 mL of deionized water into a reaction kettle with polytetrafluoroethylene as the inner lining, and reacting at 200 °C for 6 h 3+ nanoparticle solution.

[0055] S3: Preparation of GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite

[0056] GQDs / Gd2O3:Er was synthesized by adding 0.5 g of GQDs, 2 g of citric acid (CA) and 30 mL of deionized water into a reaction kettle with polytetrafluoroethylene as the inner lining, and reacting at 200 °C for 6 h 3+ The nanoparticle solution was uniformly drop-coated on the entire titanium dioxide nanometer array surface, and dried in an oven at 100 °C for 24 h to obtain GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite, namely graphene quantum dot-rare earth oxide-titanium dioxide composite material.

[0057] Example 2

[0058] The same as example 1, the difference is only that the hydrothermal temperature in S2 is 210 °C, that is, Gd2O3:Er 3+ GQDs / Gd2O3:Er was synthesized by adding 0.5 g of GQDs, 2 g of citric acid (CA) and 30 mL of deionized water into a reaction kettle with polytetrafluoroethylene as the inner lining, and reacting at 200 °C for 6 h 3+ nanoparticle solution.

[0059] Example 3

[0060] The same as example 1, the difference is only that the hydrothermal temperature in S2 is 220 °C.

[0061] Example 4

[0062] The same as example 1, the difference is only that the hydrothermal time in S2 is 7 h, that is, Gd2O3:Er 3+ GQDs / Gd2O3:Er was synthesized by adding 0.5 g of GQDs, 2 g of citric acid (CA) and 30 mL of deionized water into a reaction kettle with polytetrafluoroethylene as the inner lining, and reacting at 200 °C for 6 h 3+ nanoparticle solution.

[0063] Example 5

[0064] The same as example 1, the difference is only that the hydrothermal time in S2 is 8 h.

[0065] Example 6

[0066] The same as example 1, the difference is only that the calcination temperature in the muffle furnace in S2 is 600 °C.

[0067] Comparative Example 1

[0068] S1: Preparation of titanium dioxide nanometer array

[0069] Take 30 mL of hydrochloric acid and 30 mL of deionized water, then add 1 mL of TTIP dropwise, stir for 10 min, prepare reaction liquid A. Put FTO conductive glass and the above reaction liquid A into the reaction kettle and carry out hydrothermal reaction at 180℃ for 12h, after reaction, take out and wash the surface of FTO conductive glass substrate, and obtain titanium dioxide nanometer array.

[0070] S2: Preparation of GQDs nanoparticle solution

[0071] Put 0.5 g of citric acid into a round-bottom flask, heat in an oil bath at 200℃, after observing the conversion of citric acid solid into orange red colloid, take out the round-bottom flask, pour into 50 mL of 10 mol / L sodium hydroxide solution, stir at room temperature for 10 min until completely dissolved, and obtain orange liquid solution. Filter with 0.22 μm microporous filter membrane, and dialyze the orange liquid solution through 3500 Da dialysis bag for 3 d, replace deionized water every 8 h, until the pH value of the solution reaches 7, and obtain GQDs nanoparticle solution.

[0072] S3: Preparation of GQDs / TiO2 nanocomposite

[0073] Drop coat GQDs nanoparticle solution on titanium dioxide nanometer array, dry in an oven at 100℃ for 1 h, and finally obtain GQDs / TiO2 nanocomposite.

[0074] Comparative example 2

[0075] S1: Preparation of titanium dioxide nanometer array

[0076] Take 30 mL of hydrochloric acid and 30 mL of deionized water, then add 1 mL of TTIP dropwise, stir for 10 min, prepare reaction liquid A. Put FTO conductive glass and the above reaction liquid A into the reaction kettle and carry out hydrothermal reaction at 180℃ for 12h, after reaction, take out and wash the surface of FTO conductive glass substrate, and obtain titanium dioxide nanometer array.

[0077] S2: Preparation of Gd2O3:Er 3+ nanoparticle solution

[0078] Take 1.695 g of gadolinium chloride hexahydrate and 0.092 g of erbium chloride hexahydrate, mix and put into a distillation flask, add 200 ml of diethylene glycol, and stir magnetically at room temperature for 12 h, then add 1.44 mL of 10 mol / L sodium hydroxide solution and continue to stir for 6 hours, and synthesize Gd2O3:Er 3+ nanoparticle solution.

[0079] S3: Preparation of Gd2O3:Er 3+ / TiO2 nanocomposite

[0080] Gd2O3:Er 3+ The nanoparticle solution was drop-coated on the TiO2 nanometer array, dried in an oven at 100℃ for 24h, and finally Gd2O3:Er 3+ / TiO2 nanocomposite was obtained.

[0081] Comparative Example 3

[0082] The same as Example 1, except that the calcination temperature in S2 was 1000℃ in a muffle furnace.

[0083] The GQDs / Gd2O3:Er 3+ / TiO2 model was constructed by the CASTEP module of Materials Studio, and the composite model of the GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite obtained in Example 1 was constructed by the CASTEP module of Materials Studio. Figure 1 The differential charge density diagram thereof is shown in Figure 2 , Figure 3 Fig. 1 (a) and (b) are the band structure diagrams of TiO2 and GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite, respectively, and Fig. 1 (c) and (d) are the density of states diagrams of TiO2 and GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite, respectively. Figure 2 As shown in Fig. 1, it was found by calculation that there was an electronic interaction between GQDs / Gd2O3:Er 3+ and TiO2, Figure 2 wherein the red and blue colors respectively indicate the accumulation and loss of electrons, and the blue color appears at the interface of GQDs / Gd2O3:Er 3+ and TiO2, and the red color appears around TiO2, indicating that the electrons are transferred from GQDs / Gd2O3:Er 3+ to TiO2. GQDs / Gd2O3:Er 3+ introduced new impurity states in the band gap region of TiO2, thereby changing the electronic structure, and the decrease of the band gap is conducive to the red shift of the light absorption range, meaning that GQDs / Gd2O3:Er 3+ / TiO2 can absorb solar photons in a larger wavelength range, and the electronic transition is easier and the required excitation energy is less Figure 3 .

[0084] Figure 4 Fig. 2 is a flow chart of the preparation of the graphene quantum dot-rare earth oxide-titanium dioxide composite material of Example 1.

[0085] Figure 5 Fig. 3 is a TEM image of the GQDs / Gd2O3:Er 3+SEM and TEM images of GQDs / Gd2O3:Er / TiO2nanocomposites, wherein (a) is SEM image of TiO2, (b) is GQDs / Gd2O3:Er / TiO2 3+ SEM image of GQDs / Gd2O3:Er / TiO2, (c) is GQDs / Gd2O3:Er / TiO2 3+ TEM image of GQDs / Gd2O3:Er / TiO2, (d) is GQDs / Gd2O3:Er / TiO2 3+ HRTEM image of GQDs / Gd2O3:Er / TiO2 (the inset is SAED image), it can be seen that GQDs / Gd2O3:Er / TiO2 3+ attached on the surface of titanium dioxide. The stripe spacing of 0.21 nm and 0.19 nm correspond to (1120) plane of single graphite plane and (440) plane of cubic phase Gd2O3 respectively.

[0086] Figure 6 GQDs / Gd2O3:Er / TiO2 prepared in Example 1 3+ EDS spectrum of GQDs / Gd2O3:Er / TiO2 nanocomposites, indicating that C, O, Ti, Gd, Er elements exist and are uniformly distributed.

[0087] Figure 7 GQDs / Gd2O3:Er / TiO2 prepared in Example 1 3+ XRD pattern of GQDs / Gd2O3:Er / TiO2 nanocomposites, it can be seen that the prepared titanium dioxide is rutile type, GQDs / Gd2O3:Er / TiO2 3+ nanoparticles are monoclinic crystal structure.

[0088] Figure 8 GQDs / Gd2O3:Er / TiO2 prepared in Example 1 3+ Infrared spectrum of GQDs / Gd2O3:Er / TiO2 nanoparticles, it can be seen that all characteristic peaks of Gd2O3 and GQDs exist, which can further indicate that GQDs / Gd2O3:Er / TiO2 3+ composite nanoparticles are successfully synthesized.

[0089] Figure 9 GQDs / Gd2O3:Er / TiO2 prepared in Example 1 3+ XPS pattern of GQDs / Gd2O3:Er / TiO2 nanocomposites, wherein (a) is X-ray photoelectron full spectrum and Ti2p local magnification, (b) is C1s spectrum, (c) is O1s spectrum, (d) is Ti2p spectrum, (e) is Gd4d spectrum, (f) is Er4d spectrum, it can be seen that GQDs, Gd2O3:Er 3+ and TiO2 all exist in the prepared sample, wherein GQDs and Gd2O3 are combined through Gd-O-C bond, TiO2 and GQDs / Gd2O3:Er 3+ are combined through Ti-O-C bond, indicating that GQDs / Gd2O3:Er / TiO2 is successfully synthesized. 3+ / TiO2 nanocomposites.

[0090] Figure 10 GQDs / Gd2O3:Er prepared for Example 1 3+ Nanoparticles (a) and GQDs / Gd2O3:Er 3+ UV-Vis absorption spectrum of / TiO2 nanocomposites (b), it can be seen that GQDs / Gd2O3:Er 3+ The light absorption in the visible and infrared region has multiple peaks, which is attributed to erbium doping, indicating that erbium is successfully doped into gadolinium oxide, and GQDs / Gd2O3:Er 3+ The wavelength and intensity of TiO2 light absorption are broadened.

[0091] Figure 11 TiO2 and GQDs / Gd2O3:Er prepared for Example 1 3+ Photoluminescence spectrum of / TiO2 nanocomposites, the lower luminescence indicates that the separation of photo-generated electrons is promoted, and it can be seen that GQDs / Gd2O3:Er 3+ The recombination of photo-generated electron-hole pairs of TiO2 is inhibited.

[0092] Figure 12 TiO2 and GQDs / Gd2O3:Er prepared for Example 1 3+ Photocurrent curve (a), transient photocurrent curve (b), electrochemical impedance diagram (c) and photoelectric conversion efficiency diagram (d) of / TiO2 nanocomposites, Figure 12 (a) shows that GQDs / Gd2O3:Er 3+ The photocurrent density of / TiO2 is as high as 2.15 mA / cm 2 , which is 3.47 times that of original TiO2 (0.62 mA / cm 2 ); Figure 12 (b) shows that the prepared electrodes all have good stability and photosensitivity; Figure 12 (c) shows that the electrochemical impedance of GQDs / Gd2O3:Er 3+ / TiO2 is lower than that of TiO2, indicating that the electrons are more easily separated; Figure 12 (d) shows that the photoelectric hydrogen production efficiency of GQDs / Gd2O3:Er 3+ / TiO2 is 7.2 times higher than that of TiO2.

[0093] Figure 13 Photocurrent curve (a), transient photocurrent curve (b), electrochemical impedance diagram (c) and photoelectric conversion efficiency diagram (d) of GQDs / TiO2 nanocomposites prepared for TiO2 and Comparative Example 1. The results show that the photocurrent density of GQDs / TiO2 is 1.77 mA / cm2 Single GQDs modified TiO2 is better than GQDs / Gd2O3:Er 3+ / TiO2 photocurrent density (2.15mA / cm 2 ), 0.38mA / cm lower 2 . Mainly attributed to the lack of Gd2O3:Er 3+ The photoelectric hydrogen production efficiency of GQDs / TiO2 is also higher than that of GQDs / Gd2O3:Er 3+ / TiO2 is 41.24% lower.

[0094] Figure 14 TiO2 and Gd2O3:Er prepared in Comparative Example 2 3+ / TiO2 nanocomposite material photocurrent curve (a), transient photocurrent curve (b), electrochemical impedance spectroscopy (c) and photoelectric conversion efficiency (d). The results show that Gd2O3:Er 3+ The photocurrent density of TiO2 is 1.68 mA / cm 2 Single Gd2O3:Er 3+ Modified TiO2 and GQDs / Gd2O3:Er 3+ / TiO2 photocurrent is 0.47mA / cm lower than 2 This is mainly attributed to the lack of contribution from the excellent electrical and optical properties of GQDs. 3+ / TiO2 photoelectric hydrogen production efficiency is also higher than that of GQDs / Gd2O3:Er 3+ / TiO2 is 38.15% lower.

[0095] Depend on Figures 12-14 It can be seen that the GQDs / Gd2O3:Er prepared by the present invention 3+ / TiO2 nanocomposites are more 3+ / TiO2 has better catalytic performance and is more conducive to photoelectric hydrogen production.

[0096] Figure 15 The XRD diffraction patterns of Gd2O3 at different calcination temperatures of Example 1 (800℃), Example 6 (600℃) and Comparative Example 3 (1000℃) show that the calcination temperature will affect the crystallization properties of Gd2O3. Therefore, the preferred calcination temperature is 800℃.

[0097] The above merely provides the preferred embodiments of the present application, and the protection scope of the present application is not limited thereto, and any changes or substitutions within the technical scope disclosed by the present application should be covered within the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.

Claims

1. A method for preparing a graphene quantum dot-rare earth oxide-titanium dioxide composite material, characterized in that, Hydrothermal preparation of GQDs / Gd2O3:Er 3+ nanoparticle solution, and the GQDs / Gd2O3:Er 3+ nanoparticle solution is deposited on a titanium dioxide nanometer array, dried, to obtain GQDs / Gd2O3:Er 3+ / TiO2 nanocomposite material, namely, a graphene quantum dot-rare earth oxide-titanium dioxide composite material; The GQDs / Gd2O3:Er is prepared by the hydrothermal method 3+ The method of nanoparticle solution is as follows: The soluble gadolinium salt and the soluble erbium salt are mixed, stirred magnetically uniformly after adding diethylene glycol, and then a sodium hydroxide solution is added to continue stirring, to synthesize a nanoparticle solution in which Gd203:Er 3+ is suspended The solution of Gd2O3:Er nanoparticles suspended in water was dried to obtain a powder, which was ground and calcined to obtain Gd2O3:Er nanoparticles. 3+ The solution of Gd2O3:Er nanoparticles suspended in water was dried to obtain a powder, which was ground and calcined to obtain Gd2O3:Er nanoparticles. 3+ The solution of Gd2O3:Er nanoparticles suspended in water was dried to obtain a powder, which was ground and calcined to obtain Gd2O3:Er nanoparticles. The Gd2O3:Er 3+ GQDs / Gd2O3:Er were prepared by hydrothermal method 3+ nanoparticle solution; The soluble gadolinium salt is gadolinium chloride hexahydrate, and the soluble erbium salt is erbium chloride hexahydrate; The temperature of the calcination is 600-800 DEG C, and the time is 2h; The Gd2O3:Er 3+ The mass ratio of nanoparticles to citric acid was 1:20; Hydrothermal preparation of GQDs / Gd2O3:Er 3+ The temperature of the hydrothermal reaction is ≥200℃ and the time of the hydrothermal reaction is ≥6h when the nanoparticle solution is used. 2.The method for preparing graphene quantum dots-rare earth oxide-titanium dioxide composite material according to claim 1, characterized in that, The preparation method of the titanium dioxide nanometer array is as follows: Mix hydrochloric acid and deionized water, then add titanium isopropyl titanate drop by drop, stir uniformly, and prepare reaction liquid A; Mix the substrate with the reaction liquid A and perform hydrothermal reaction, take out and wash the surface of the substrate, and obtain the titanium dioxide nanometer array. 3.The method of claim 2, wherein the graphene quantum dot-rare earth oxide-titanium dioxide composite material is prepared by the following steps: (a) preparing a graphene quantum dot-rare earth oxide composite material; and (b) mixing the graphene quantum dot-rare earth oxide composite material with titanium dioxide to obtain the graphene quantum dot-rare earth oxide-titanium dioxide composite material. The volume ratio of the titanium isopropyl titanate, deionized water and hydrochloric acid is 1:30:

30. 4.The method of claim 2, wherein the graphene quantum dot-rare earth oxide-titanium dioxide composite material is prepared by the following steps: (a) preparing a graphene quantum dot-rare earth oxide composite material; and (b) mixing the graphene quantum dot-rare earth oxide composite material with titanium dioxide. When the substrate is mixed with the reaction liquid A to perform hydrothermal reaction, the temperature of the hydrothermal reaction is greater than or equal to 180 DEG C, and the time of the hydrothermal reaction is greater than or equal to 12h.

5. Application of the graphene quantum dot-rare earth oxide-titanium dioxide composite material prepared by the method in any one of claims 1-4 in photoelectric hydrogen production.

Citation Information

Patent Citations

  • Preparation method of quantum dot cellulose-based photocatalytic composite material

    CN106694040A

  • Polymer composite membrane material with photocatalytic activity and preparation method thereof

    CN111215140A